SISTEM PENGELOLAAN KLUB BASKET DI PALANGKA RAYA BERBASIS WEB 2.0 - Devi Karolita; Sherly Christina; Deviana Agustin Rimi (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2014)
Basketball club management system in Palangka Raya based on web 2.0 is used as aninformation media of Persatuan Bola Basket Indonesia (PERBASI) of Palangka Raya to shareinformation about the development of the basketball in Palangka Raya, club and player datainformation, event that will take place. The system also provides data management event, datamanagement schedules, data management scores, data management statistics of players, datamanagement club's performance, data management e-ticketing. Statistical data can be known from thebest players based on the assessment criteria, and the player statistics will be managed to obtain the clubperformance values. Features of e-ticketing is provided to facilitate the purchase of a ticket